A Maturity Model for Assessing the Digitalization of Public Health Agencies - Eileen Doctor; Torsten Eymann; Daniel Fürstenau; Martin Gersch; Kristina Hall; Anna Lina Kauffmann; Matthias Schulte-Althoff; Hannes Schlieter; Jeannette Stark; Katrin Wyrtki (Business & Information Systems Engineering, 2023)
Requests for a coordinated response during the COVID-19 pandemic revealed the limitations of locally-operating public health agencies (PHAs) and have resulted in a growing interest in their digitalization. However, digitalizing PHAs – i.e., transforming them technically and organizationally – toward the needs of both employees and citizens is challenging, especially in federally-managed local government settings. This paper reports on a project that develops and evaluates a continuous (vs. a staged) maturity model, the PHAMM, for digitalizing PHAs as a cornerstone of a digitally resilient public health system in the future. The model supports a coordinated approach to formulating a vision and structuring the steps toward it, engaging employees along the transformation journey necessary for a federally-managed field. Further, it is now being used to allocate substantial national funds to foster digitalization. By developing the model in a coordinated approach and using it for distributing federal resources, this work expands the potential usage cases for maturity models. The authors conclude with lessons learned and discuss how the model can incentivize local digitalization in federal fields.
Keywords: 000; Digital maturity; Digitalization; Public health offices; Maturity models